Photocatalytic activity of nickel catalyst toward remazol brilliant blue dye in various pH conditions - Muhammad Farhan, Hanafi; Norzahir, Sapawe (Elsevier Ltd., 2020)
The pH of solution plays an important role in the photocatalytic degradation of organic pollutants which influences the surface-charge properties of the catalysts. In this study, EGNiO shows remarkable photodegradation at pH 3 (89.1%), but further increase pH up to pH 11 resulted in decreases in degradation rate. The electrostatic interaction between anionic RBB with surface charge of catalyst shows significant effects, apart from the formation of hydroxyl radicals. Good photoactivity reveals the potential of EGNiO catalyst to be used as the environmental catalyst.